INFLUÊNCIA DO Nb2O5 NO COMPORTAMENTO VARISTOR DO SISTEMA TiO2 - Cr2O3 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
The aim of this paper is to analyse the doping influence by Nb2O5 on the varistor system behaviour (99,50-x)%TiO2.(0,05)%Cr2O3.(x)%Nb2O5, when x={0,10%; 0,15%; 0,20%; 0,25%} mol. Powder processing techniques were used to prepare the varistors. Ball milling process were used to mix the reagents in a alcoholic media. Then they were isostatically pressed at 210MPa and then sintered in air at 1400C for two hours at 5C cooling rate, which produced pellets with high densification. Electric data, which was obtained by continued currents at different temperatures, showed for lower concentration x=0,10% the values ER=4,41V/cm and 4,6, and for the higher concentration x=0,25% ER=9,71V/cm and 15,3. Furthermore, it was possible to see changes on the barrier potential, from which its height became higher and its width became slimmer as the doping element concentration was increased. As opposed to the experiment described above, for x=0,25%, significant reduction on potential barrier height and on barrier breakdown voltage was observed. More over, the tendency of unit cell volume, which growth with higher doping element concentration, was broken for x=0,25% composition. These facts left us to think that could be happening little Nb2O5 segregations to grain boundaries, or the reduction in the average grains sizes for this composition could be reducing the concentrations of Nb2O5 at grain boundaries. The Rietveld method was used to refine the X-ray data, which supplied lattice parameters with great accuracy. This method did not enable us to find other phases apart from rutile titanium dioxide. The M.E.V. micrographs were used to measure the average grains sizes, and it was found average grains sizes between 7 and 16 Moreover, it was possible to notice that larger grains occurred with bigger doping element concentrations chaperoned by greater varistorporosity and lower grains form uniformity.
Keywords: varistor; varistor; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA